2023
DOI: 10.1021/acscentsci.2c01136
|View full text |Cite
|
Sign up to set email alerts
|

Powerful Avidity with a Limited Valency for Virus-Attachment Blockers on DC-SIGN: Combining Chelation and Statistical Rebinding with Structural Plasticity of the Receptor

Abstract: The C-type lectin receptor DC-SIGN has been highlighted as the coreceptor for the spike protein of the SARS-CoV-2 virus. A multivalent glycomimetic ligand, Polyman26, has been found to inhibit DC-SIGN-dependent trans-infection of SARS-CoV-2. The molecular details underlying avidity generation in such systems remain poorly characterized. In an effort to dissect the contribution of the known multivalent effects  chelation, clustering, and statistical rebinding  we studied a series of dendrimer constructs relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…In the current study, thermodynamic characterization of the highest affinity glycomimetic 2 by ITC revealed significant enthalpic stabilization that was partially compensated by entropic destabilization, when compared to its analogue 1 (Figure ). Notably, both glycomimetics are preorganized for chelation binding; however, 2 has increased ligand valency (Figure ).…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…In the current study, thermodynamic characterization of the highest affinity glycomimetic 2 by ITC revealed significant enthalpic stabilization that was partially compensated by entropic destabilization, when compared to its analogue 1 (Figure ). Notably, both glycomimetics are preorganized for chelation binding; however, 2 has increased ligand valency (Figure ).…”
mentioning
confidence: 54%
“…Too flexible a linker, however, can incur significant entropic cost depending on the number of rotatable bonds in the linker that become frozen post binding. The findings of the current study also suggest the HIV-1 targeting conjugate and other avidity targeting conjugates for viral spike proteins may benefit from additional degenerate binding ligands and alternative topologies to increase statistical rebinding events.…”
mentioning
confidence: 67%
See 3 more Smart Citations